Dampak Minuman Keras (Tuak) Terhadap Ketertiban Masyarakat Desa Batunajagar, Kecamatan Sijamapolang Kabupaten Humbang Hasundutan - Helen Mona Romaito Pakpahan; Apeles Lexi Lonto; Theodorus Pangalila (CV. Kurnia Grup, 2026)
The purpose of this study is to determine the impact of alcoholic beverages (tuak) on public order in Batunajagar Village, Sijamapolang District, Humbang Hasundutan Regency, and to identify the factors influencing the disruption of social order caused by tuak consumption. This study employs a qualitative research method with a descriptive approach. Data were collected through interviews, observations, and documentation. The results show that excessive consumption of tuak has negative impacts on public order, including deviant behaviors such as fights, theft, noise disturbances, and damage to public facilities. In addition, it reduces the sense of safety and comfort within the community and disrupts social relationships among residents. The factors influencing these conditions include environmental influences, habitual behavior, lack of supervision, and low public awareness of the negative effects of alcoholic beverages. Therefore, active roles from the village government and the community are needed in supervision, guidance, and raising awareness to minimize the negative impacts of tuak consumption on public order